On Issue of IT–Specialists’ Training in Classical Universities - Vladymyrova, M.V.; Spivakovskiy, A.V.; Zaretskaya, I.T.; Zholtkevych, G.N. (Journal of Information Technologies in Education (ITE), 2008)
The paper is devoted to the problems of IT-specialists training in Ukrainian universities. It discusses the weights of different knowledge areas in its body of knowledge stemming from the stated in the paper abilities and skills required from modern IT-specialist. The example of curriculum which includes sufficient fundamental mathematical training, covers the core of CC2001 in computer science field and thus provides for all required skills is offered.